Artemether ameliorates type 1 diabetic liver injury alongside the associated defects in mitochondrial ultrastructure and central carbon metabolism - Qike Fu; Jiaxin Li; Xiufen Gu; Yating Zhang; Pengxun Han; Xuewen Yu; Mumin Shao; Huili Sun; Yuchun Cai (PLoS ONE, 2026)
Type 1 diabetes mellitus (T1DM) is characterized by autoimmune-mediated destruction of pancreatic islet β-cells and the resultant absolute insulin deficiency, which leads to systemic metabolic dysregulation. Hepatic injury has emerged as a clinically significant complication of T1DM; however, no targeted therapeutic intervention is currently available. Artemether (Art), a methyl ether derivative of artemisinin, has shown potential in ameliorating hyperglycemia, but its efficacy in mitigating T1DM-associated hepatic dysfunction remains insufficiently elucidated. This study comprehensively evaluates the hepatoprotective effects of Art in a murine model of T1DM, with particular emphasis on mitochondrial structural integrity and the regulation of glucose and lipid metabolism. Hepatic function was assessed through histopathological evaluation, ultrastructural examination of mitochondria via transmission electron microscopy, and molecular analysis of gene and protein expression levels. Metabolic intermediates associated with glucose and lipid metabolic pathways were quantitatively analyzed using ultra-high-performance liquid chromatography coupled with triple quadrupole tandem mass spectrometry (UPLC-QQQ-MS/MS). Administration of Art significantly attenuated both diabetic manifestations and liver injury. Importantly, Art preserved mitochondrial morphology, restored the expression of some proteins related to the respiratory chain complex, and downregulated indicators of hepatic fatty acid β-oxidation, upregulated markers of de novo fatty acid synthesis, normalized intrahepatic triglyceride concentrations, and reduced expression of key molecules involved in gluconeogenesis and glycogenolysis. These findings indicate that Art confers protective effects against liver injury in T1DM through coordinated modulation of mitochondrial function and key metabolic pathways at transcriptional, translational, and metabolic intermediate levels.